2011
DOI: 10.3892/ijo.2011.1168
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activity of fucoidan is mediated by nitric oxide released from macrophages

Abstract: Abstract. Fucoidan, a sulfated polysaccharide, has significant cytotoxic activity against tumor cells; however, the mechanism(s) of this action remains poorly understood. The present study was designed to determine the in vitro and in vivo effects of fucoidan and their molecular mechanisms. Fucoidan from Cladosiphon okamuranus Tokida cultivated in Okinawa, Japan, delayed tumor growth in Sarcoma 180 (S-180)-bearing mice. However, it failed to inhibit S-180 cell growth in vitro. Activated macrophages are known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…These data suggest that fucoidan may have the ability to enhance not only direct presentation of OVA by CD8α − cDCs but also cross-presentation of OVA by CD8α + cDCs. Since fucoidan can induce activation of macrophages [28] and other DC populations, such as langerhans cells (LCs), that are also able to cross-prime CTLs [29], [30], we are currently investigating whether fucoidan can induce CTL responses in mice that are depleted of macrophage and LCs.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that fucoidan may have the ability to enhance not only direct presentation of OVA by CD8α − cDCs but also cross-presentation of OVA by CD8α + cDCs. Since fucoidan can induce activation of macrophages [28] and other DC populations, such as langerhans cells (LCs), that are also able to cross-prime CTLs [29], [30], we are currently investigating whether fucoidan can induce CTL responses in mice that are depleted of macrophage and LCs.…”
Section: Discussionmentioning
confidence: 99%
“…Additional in vivo studies carried out in different models of colon, hepatocellular, sarcoma and leukemia cancer cells have also described positive effects for oral ingestion of fucoidans, although these were not from Fucus spp. origin [119,120,121]. …”
Section: Nutrient Composition Of Fucus Sppmentioning
confidence: 99%
“…Fucoidan was found to prevent diethylnitrosamine-induced hepatocarcinogenesis by inhibiting metabolic activation of the carcinogen [30]. Takeda et al found that oral administration of fucoidan effectively inhibited growth of implanted Sarcoma-180 cells in xenograft mouse models [31]. Fucoidan likely mediated nitric oxide (NO) release by stimulated macrophages in the tumor microenvironment, thus causing apoptosis.…”
Section: In Vivo Anticancer Effectsmentioning
confidence: 99%
“…Furthermore, supernatants from fucoidan-stimulated macrophages were found to cause apoptosis of Sarcoma-180 cells. This effect was negated by the addition of a NO synthase inhibitor, N G -nitro- l -arginine methyl ester ( l -NAME) [31]. Xue et al demonstrated that β-catenin expression in tumor lesions was decreased significantly by fucoidan treatment of tumor-bearing mice [36].…”
Section: In Vivo Anticancer Effectsmentioning
confidence: 99%